Letter from the editor - van Heerden, Martina (WritingThreeSixty, 2021)
Welcome to the second issue of WritingThreeSixty for 2020. This special issue is centred around the theme of the Covid-19 Lockdown which has affected all of us. After our call for papers in the previous issue, we received a record number of submissions. Interestingly, poetry was overwhelmingly the preferred medium for expressing thoughts on the effects of lockdown. In this issue, you will find a selection of poems, as well as a short story and a research article. This will be my last issue as editor-in-chief; I hand the reins over to Stephanie Williams, our social media manager. I have been with WritingThreeSixty since 2015 and I have thoroughly enjoyed my time with it. I leave knowing that the journal is in very capable hands! Best Wishes, Editor-in-chief Martina van Heerden